2012
DOI: 10.1007/s11605-011-1784-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Preoperative Neoadjuvant Concurrent Chemoradiation Therapy on Margin-Negative Resection in Borderline Resectable Pancreatic Cancer

Abstract: Pancreatectomy following preoperative neoadjuvant CCRT can be a potential strategy for margin-negative resection in BRPCa patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…Neoadjuvant therapy has been reported to lead to a decrease in the number of metastatic LNs, as well as higher R0 rates. 10,19,33 Indeed, the R0 rate and PFS in BRPC-A patients who underwent neoadjuvant therapy followed by surgical resection were significantly better than those with upfront surgery in this study. However, our results showed that the rate of LN metastasis and LNR were similar between the BRPC-A patients undergoing surgical resection with and without neoadjuvant therapy, and the OS did not significantly differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 47%
“…Neoadjuvant therapy has been reported to lead to a decrease in the number of metastatic LNs, as well as higher R0 rates. 10,19,33 Indeed, the R0 rate and PFS in BRPC-A patients who underwent neoadjuvant therapy followed by surgical resection were significantly better than those with upfront surgery in this study. However, our results showed that the rate of LN metastasis and LNR were similar between the BRPC-A patients undergoing surgical resection with and without neoadjuvant therapy, and the OS did not significantly differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 47%
“…After a median follow-up of 13.4 months, the 1-year progression-free survival was 83 % and the 1-year overall survival was 100 %. Table 2 shows results of some key studies of neoadjuvant strategy in patients with pancreatic cancer [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The pragmatic trial from the Intergroup would throw light on how to manage these patients optimally-all patients with borderline resectable pancreatic cancer receive FOLFIRINOX for 4 cycles followed by chemoradiotherapy with capecitabine and if stable or responding, patients are taken for surgery 6-8 weeks post-completion of radiotherapy.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…The International Study Group of Pancreatic Surgery likewise does not support neoadjuvant therapy regimens in borderline resectable pancreatic cancer (BRPC) patients with isolated venous involvement if technical options of resections are possible. 4 Nonetheless, despite a paucity of prospective data to support a standard treatment regimen for borderline resectable pancreatic cancer, neoadjuvant therapy is currently the preferred initial approach in the United States, 25,[43][44][45][46][47][48][49] and was recommended by the expert consensus statement sponsored by the AHPBA, SSAT, and SSO. 41 The rationale for pursuing preoperative treatment for patients with borderline resectable PDAC is similar to that for patients with potentially resectable pancreatic cancer, but a greater emphasis is placed on maximizing the potential for R0 resection.…”
Section: Rationale For Preoperative Therapymentioning
confidence: 99%
“…45,51 Therefore, although data are few with regard to the sequencing and duration of preoperative treatment modalities, most agree that a treatment schema that incorporates systemic chemotherapy and chemoradiation is the optimal strategy, and this notion has been embraced by several institutions and high-volume pancreatic cancer treatment centers ( Table 2). 25,[43][44][45][46][47][48][49] Metrics of Response to Neoadjuvant Therapy When neoadjuvant therapy is administered, patients should be staged before initiation and after completion of therapy (chemotherapy, chemoradiation, or both). 52,53 Changes in the patient's clinical or biologic status or the radiographic findings at the time of restaging may necessitate a reassessment of the treatment plan.…”
Section: Rationale For Preoperative Therapymentioning
confidence: 99%